Blood creatinine and urea nitrogen at ICU admission and the risk of in-hospital death and 1-year mortality in patients with intracranial hemorrhage - Luo, Hai; Yang, Xuanyong; Chen, Kang; Lan, Shihai; Liao, Gang; Xu, Jiang (Frontiers in Cardiovascular Medicine, 2022)
Background: The relationship between renal function and clinical outcomes in patients with cerebral hemorrhage is controversial. Aims: We investigated the associations of blood creatinine and urea nitrogen levels with hospital death and 1-year mortality in patients with cerebral hemorrhage treated in the intensive care unit (ICU). Methods: A total of 2682 patients with cerebral hemorrhage were included from the Medical Information Mart for Intensive Care III (MIMIC-III) database. Clinical variables, including admission creatinine, urea nitrogen, type of cerebral hemorrhage, underlying diseases and other blood biochemistry parameters, were collected. Multivariable correction analysis was conducted of the relationships between blood creatinine and urea nitrogen levels on admission with hospital death and 1-year mortality in the included patients with cerebral hemorrhage. Smooth curve and subgroup analyses were also performed for these associations. Results: A total of 2682 patients had their blood creatinine and urea nitrogen levels measured within the first 24 h after ICU admission, with median values of 0.80 mg/dL and 5.00 mg/dL, respectively. We observed steeply linear relationships between creatinine and urea nitrogen levels and the risk of in-hospital death and 1-year mortality, but the risk of in-hospital mortality and 1-year mortality increased little or only slowly above creatinine levels >1.9 mg/dL or urea nitrogen >29 mg/d (the inflection points). Consistently, conditional logistic regression analysis suggested that these inflection points had significant modification effects on the associations between blood creatinine levels, as well as blood urea nitrogen, and the risk of in-hospital death (interaction value<0.001) and 1-year mortality (interaction value<0.001). Conclusion: Our results supported the hypothesis that elevated blood creatinine and urea nitrogen levels on admission are associated with an increased risk of in-hospital death and 1-year mortality in patients with cerebral hemorrhage. Interestingly, these independent relationships existed only for lower levels of serum creatinine (<1.9 mg/dL) and uric acid (<29 mg/dL).